Development of mind mapping-based comics to improve math learning outcomes - Trimurtini Trimurtini; Mira Amalia Setyani; Elok Fariha Sari; Nursiwi Nugraheni (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2021)
This study aims to develop, study the feasibility and effectiveness of mathematics comic media based on mind mapping for fifth-grade students of public elementary schools in Demak. The method used is the Sugiyono Research and Development model consisting of 7 steps. The data analysis technique used descriptive statistics, t-test, z-test and n-gain. The results showed the development process of mathematical comic media based on mind mapping on speed and discharge topics with the local cultural background of Demak city. Media was assessed by material, media, and language experts, and It showed valid results and very feasible to be implemented.  This media's effectiveness is indicated by the improvement of the Students’ learning outcomes and learning achievement.  Students and teachers' response about this media shows positive responses because the comic media are practical and complete content, such as (material, question, assignment, solution, and evaluation). The conclusion is learning media has been successfully developed.    Mathematics comic media based on mind mapping is very feasible and practical used in learning mathematics, and it is efeffectively improvements’ learning.